Strategi Pengembangan Sarana dan Prasarana Madrasah Unggul Berbasis Kebijakan Nasional - Yu’ti Af’idah; Kadi, Titi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of educational facilities and infrastructure is one of the essential factors in realizing excellent madrasahs capable of competing in the modern educational era. National policies through the Ministry of Religious Affairs of the Republic of Indonesia have given significant attention to improving the quality of madrasah facilities and infrastructure through various programs such as SBSN funding assistance, madrasah digitalization, and strengthening school-based management. This study aims to analyze strategies for developing facilities and infrastructure in excellent madrasahs based on national policies using a literature study approach on various scientific journals published within the last five years. The results show that the development strategies are carried out through needs-based planning, optimization of infrastructure management, utilization of information technology, increased community participation, and government policy support through national funding programs. The implementation of these strategies has an impact on improving the quality of learning, public trust, and the competitiveness of madrasahs. However, several obstacles remain, including limited budgets, human resources, and unequal distribution of facilities among madrasahs. Therefore, synergy among the government, madrasah principals, teachers, and the community is needed in sustainable facilities and infrastructure development.